2014
DOI: 10.1177/1403494814550517
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between fitness and health-related quality of life and the mediating role of self-determined motivation in overweight adolescents

Abstract: This file was dowloaded from the institutional repository Brage NIH -brage.bibsys.no/nih Riiser, K., Ommundsen, Y., Småstuen, M. C., Løndal, K., Misvaer, N., Helseth, S. (2014). The relationship between fitness and health-related quality of life and the mediating role of self-determined motivation in overweight adolescents. The relationship between fitness and health-related quality of life and the mediating role of self-determined motivation in overweight adolescentsAim: To examine the relationship between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 26 publications
3
17
0
7
Order By: Relevance
“…Our results confirm and extend previous cross‐sectional evidence on the positive association between cardiorespiratory fitness and HRQoL (Guedes et al, ; Marques et al, ; Padilla‐Moledo et al, ; Riiser et al, ). These results underscore the potential modifying effect of cardiorespiratory fitness on HRQoL during adolescence and may be clinically relevant to adolescents' psychological well‐being.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results confirm and extend previous cross‐sectional evidence on the positive association between cardiorespiratory fitness and HRQoL (Guedes et al, ; Marques et al, ; Padilla‐Moledo et al, ; Riiser et al, ). These results underscore the potential modifying effect of cardiorespiratory fitness on HRQoL during adolescence and may be clinically relevant to adolescents' psychological well‐being.…”
Section: Discussionsupporting
confidence: 92%
“…Several cross‐sectional studies of youth have shown a positive association between cardiorespiratory fitness and HRQoL (Guedes et al, ; Marques, Mota, Gaspar, & de Matos, ; Padilla‐Moledo et al, ; Riiser et al, ). However, despite of these findings, data from prospective studies are insufficient with regard to impact of changes in cardiorespiratory fitness on adolescents' HRQoL.…”
Section: Introductionmentioning
confidence: 99%
“…However, the main purpose of this study was to examine the relationship between CRF, mental HRQoL, and resilience, and how resilience acts as a partial mediating step between CRF and mental HRQoL. A similar study found that self‐determined motivation, but not body image, is a mediator variable in the relationship between fitness and HRQoL in overweight adolescents (Riiser et al, ).…”
Section: Discussionmentioning
confidence: 96%
“…In addition, our study found a positive association between CRF and the MCS of HRQoL. There are several studies that support this relationship (Hakkinen et al, ; Riiser et al ., ). Of these, a systematic review concluded that there is consistent evidence of the association between high levels of physical activity or physical fitness (defining the latter as an indirect indicator of physical activity level, and a biologic phenotype affected by both physical activity and genetics) and better scores in various dimensions of HRQoL, including the mental dimension, in the general adult population (Bize et al, ).…”
Section: Discussionmentioning
confidence: 97%
“…The MSFT has become widely used as a field test in both athletic and occupational settings [177–179]. The test assesses VO 2 max, which is calculated using the level achieved during the test [167] that is cross referenced with a table of oxygen uptake values [180].…”
Section: Physical Fitnessmentioning
confidence: 99%